Characterization of Candida spp. isolated from the bloodstream in a reference hospital in Brazil: using MALDI-TOF/MS to identify unusual species of Candida (Research, Society and Development, 2022)
Candidemia is a health problem with a high mortality rate. The aims of this study were to compare the identification of Candida spp. via traditional methodologies and mass spectrometry (MALDI-TOF/MS) in order to verify the antifungal susceptibility profile of these isolates and analyze the clinical evolution of patients. This was a two-year prospective cohort conducted at the Hospital de Clínicas de Uberlândia (HCU-UFU). Candida spp. were identified via VITEK®-2 and MALDI-TOF/MS. Antifungal susceptibility tests were conducted via VITEK®-2. Clinical-demographic data were assessed from medical records and variables were described as mean, standard deviation, frequency and percentage, and risk factors were evaluated using univariate and multivariate analysis. A total of 113 patients and 126 Candida spp. isolates were studied. C. albicans was most frequent (30%); MALDI-TOF/MS identified unusual species, including misidentification of C. famata. Most of the isolates (95%) were susceptible to the tested antifungals. Most patients were men (65%) and older than 60 years of age (45%); 85% of patients were treated with fluconazole. The 30-day mortality rate was 56%; patients who did not receive treatment and those who started later had a lower survival rate (p